The Influence Of Brand Image And Trust On The Purchase Decision Of Honda Genio Motorcycle At PT. Astra International TBk. Honda Branch All - Tiara Puspita Sari; Heri Fitriadi; Delvina Yulanda (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the Influence of Brand Image and Trust on the Decision to Buy Honda Genio Motorcycles at PT. Astra International T.bk Honda Lahat Branch either partially or simultaneously. This study is a quantitative associative research using the slovin formula method in determining samples. The sample used in this study amounted to 70 people who were used as research respondents. Based on the results of the study, the regression equation Y = 2.942 + 0.438 X1 + 0.476 X2 + e, means that without the variables Brand Image (X1) and Trust (X2), the Purchase Decision (Y) is 2.942. The value of the determination coefficient (R2) is 0.754, meaning that the independent variables have a contribution with the dependent variable of 75.4% and the remaining 24.6% is influenced by other factors that were not studied by the author. Based on the results of SPSS version 25.0 processing, the Fcal value was obtained of 102.499 while the Ftable value was 3.134 thus 102.499 > 3.134, Ho was rejected and Ha was accepted, meaning that the variables of Brand Image (X1) and Trust (X2) together had a significant effect on the Purchase Decision (Y). The Ttable value is 1.668. By comparing the values of Thitung and Ttabul, it can be concluded: the Brand Image variable (X1) with the value of Tcal > Ttable or 3.534 > 1.668 , then Ho is rejected and Ha is accepted. Trust (X2) with a Thcal value of > Ttable or 3.943 > 1.668, then the Brand Image (X1) and Trust (X2) variables have a partial effect on the Purchase Decision (Y) of Honda Genio Motorcycle at PT. Astra International T.bk Honda Branch All.